Outshine to Outbid: Weather-Induced Sentiment and the Housing Market - Hu, Maggie Rong; Lee, Adrian D. (Management Science, 2020)
This paper examines how sentiment affects homebuyers’ housing transaction decisions with a focus on auction sales. Utilizing housing transaction data in Sydney from 2000 to 2014, we find that transaction prices are significantly higher for auction sales compared with private sales, consistent with the notion of a “winner’s curse.” Four sentiment proxies, including three weather-based sentiment proxies and a survey-based sentiment index, are used to derive novel measures of sentiment, revealing that higher sentiment is associated with higher transaction prices, particularly for auction sales. Moreover, sentiment boosts sale prices particularly when the housing market is in boom; however, investors are not more prone to sentiment bias than are owner-occupiers. Sentiment exhibits an asymmetric effect in that low sentiment dampens price to a greater extent compared with the price-boosting effect of high sentiment. Our result is robust to using national sport events as sentiment shocks, selection bias, and participation constraints. Potential mechanisms include present-biased preferences and sentiment-related projection bias. Overall, our evidence sheds light on the role of sentiment in housing market decisions. This paper was accepted by Tyler Shumway, finance.